Cost-effective analysis of preliminary single-operator cholangioscopy for management of difficult biliary stones - Sljivic, Igor; Trasolini, Roberto; Donnellan, Fergal (Endoscopy International Open, 2022)
Background and study aims Single-operator peroral cholangioscopy (SOC) is a therapeutic modality for difficult biliary stone disease. Given its high success rate and increasing availability, analysis of the economic impact of early SOC utilization is critical for clinical decision-making. Our aim is to compare the cost-effectiveness of different first and second-line endoscopic modalities for difficult-to-treat choledocholithiasis.Patients and methods A decision-tree model with a 1-year time horizon and a hypothetical cohort of 200 patients was used to analyze the cost-effectiveness of SOC for first, second and third-line intervention in presumed difficult biliary stones. We adopted the perspective of a Canadian tertiary hospital, omitting recurrence rates associated with endoscopic retrograde cholangiopancreatography (ERCP). Effectiveness estimates were obtained from updated meta-analyses. One-way sensitivity analyses and probabilistic sensitivity analyses were also performed to assess how changes in key parameters affected model conclusions.Results First- and second-line SOC achieved comparable clinical efficacy from 96.3 % to 97.6% stone clearance. The least expensive strategy is third-line SOC (SOC-3: $800,936). Performing SOC during the second ERCP was marginally more expensive (SOC-2: $ 816,584) but 9 % more effective. The strategy of first-line SOC incurred the highest hospital expenditures (SOC-1: $ 851,457) but decreased total procedures performed by 16.9 % when compared with SOC-2. Sensitivity analysis was robust in showing SOC-2 as the most optimal approach.Conclusions Second-line SOC was superior to first and third-line SOC for treatment of difficult biliary stones. When based on meta-analysis of non-heterogeneous trials, SOC-2 is more cost-effective and cost-efficient. Our study warrants a larger pragmatic effectiveness trial.